A geomimetic synthesis of mellite: a mineral containing a benzene ring. (1st May 2015) - Plater, M. John; Harrison, William
The synthesis of mellite from mellitic acid, KOH and Al2(SO4)318H2O is demonstrated and discussed as a potential geomimetic process for the formation of the mineral mellite in brown coal. The single crystal structures and IR spectra of the mineral mellite and of synthetic mellite are identical.